Percutaneous transthoracic catheter drainage prior to surgery in treating neonates with congenital macrocystic lung malformation presenting with respiratory distress - He, Taozhen; Sun, Xiaoyan; Luo, Dengke; Dai, Shiyi; Yuan, Miao; Yang, Gang; Cheng, Kaisheng; Xu, Chang (Frontiers in Pediatrics, 2023)
Backgound: It is rarely seen that neonates with congenital macrocystic lung malformation(CMLM) presenting with respiratory distress require emergency intervention. No consensus has been achieved concerning the best policy facing such condition. This study aims to evaluate the efficacy and safety of our strategies in treating neonates with CMLM presenting with respiratory distress. Methods: We retrospectively reviewed the data of six neonates with CMLM presenting with respiratory distress from April 2020 to October 2022 for whom drainage-prior-to-surgery strategy were adopted and favorable outcomes were obtained. The relevant data was reviewed and analyzed. Results: All the patients were prenatally diagnosed with congenital lung malformation and postnatally as congenital macrocystic lung malformation via CT scan. Each neonate accepted percutaneous thoracic catheter drainage prior to surgery. The first and fifth neonates with macrocystic lung mass experienced prompt open lobectomy and delayed thoracoscopic surgery due to failure of air drainage, respectively. The other four patients obtained good drainage of the large air-filled cyst, thus gaining the opportunity for elective thoracoscopic surgery within median 45 d. Conclusions: For neonates with macrocystic lung malformation presenting with respiratory distress due to mediastinal compression, percutaneous thoracic catheter drainage is worth a shot for elective thoracoscopic surgery due to its feasibility and safety.CMLM, congenital macrocystic lung malformation PTCD, percutaneous transthoracic catheter drainage CPAM, congenital pulmonary airway malformation EXIT, ex-utero intrapartum treatment ECMO, extracorporeal membrane oxygenation CVR, CPAM volume ratio CLM, Congenital lung malformations